Potential Mechanism for HIV-Associated Depression: Upregulation of Serotonin Transporters in SIV-Infected Macaques Detected by 11C-DASB PET - Swati Shah; Sanhita Sinharay; Kenta Matsuda; William Schreiber-Stainthorp; Siva Muthusamy; Dianne Lee; Paul Wakim; Vanessa Hirsch; Avindra Nath; Michele Di Mascio; Dima A. Hammoud (Frontiers in Psychiatry, 2019)
Purpose: Increased incidence of depression in HIV+ patients is associated with lower adherence to treatment and increased morbidity/mortality. One possible underlying pathophysiology is serotonergic dysfunction. In this study, we used an animal model of HIV, the SIV-infected macaque, to longitudinally image serotonin transporter (SERT) expression before and after inoculation, using 11C-DASB (SERT ligand) PET imaging.Methods: We infected seven rhesus macaques with a neurovirulent SIV strain and imaged them at baseline and multiple time points after inoculation (group A). Pyrosequencing methylation analysis of the SERT promoter region was performed. We also measured SERT mRNA/protein in brain single-cell suspensions from another group (group B) of SIV-infected animals (n = 13).Results: Despite some animals showing early fluctuations, 86% of our group A animals eventually showed a net increase in midbrain/thalamus binding potential (BPND) over the course of their disease (mean increased binding between last time point and baseline = 30.2% and 32.2%, respectively). Repeated-measures mixed-model analysis showed infection duration to be predictive of midbrain BPND (p = 0.039). Thalamic BPND was statistically significantly associated with multiple CSF cytokines (P < 0.05). There was higher SERT protein levels in the second group (group B) of SIV-infected animals with SIV encephalitis (SIVE) compared to those without SIVE (p = 0.014). There were no longitudinal changes in SERT gene promoter region percentage methylation between baselines and last time points in group A animals.Conclusion: Upregulated SERT leading to lower synaptic levels of serotonin is a possible mechanism of depression in HIV+ patients, and extrapolating our conclusions from SIV to HIV should be sought using translational human studies.